How do students’ beliefs about mathematics ability change in their first year at university? - Campbell, Anita (Critical Studies in Teaching and Learning, 2023)
The affective dimension of students’ transition into university is an area of development that has the potential to improve student success. Large-scale research suggests that developing a growth mindset belief –that academic ability can always be expanded–may be especially helpful for first generation students. A starting point for developing growth mindsets as one type of affective support for students is to investigate how we can position students on the fixed-to-growth spectrum of beliefs about academic ability. This mixed-methods study considers the changes during their first year of university in the mindset beliefs held by two representative first-year mathematics students, one who passed and one who had to repeat the second semester of mathematics. Without experiencing interventions aimed at developing growth mindsets, both students showed small shifts towards stronger growth mindsets over their first year. Limitations with assessing mindsets are acknowledged and recommendations for future research in this area are suggested.